Politik Hukum Penggunaan Sanksi Pidana Penjara Dalam Pperundang-Undangan Di Indonesia - M. Ilham Adepio (Jurnal Ilmiah Kutei, 2024)
In the enforcement of criminal law in Indonesia, imprisonment is the most dominant punishment imposed by judges to criminal defendants, if referring to the Criminal Code. However, in addition to the Criminal Code, which is the master book of criminal law regulations in Indonesia, there are other regulations governing criminal provisions, namely regulations in the form of laws. The law is a product of the Legislative Body as an institution authorised to hold the power to make laws. Each term of office of the House of Representatives (DPR) always issues products in the form of laws, some of which regulate criminal provisions with elements of penal reform which are part of the policy/politics of criminal law (penal policy). In 2017-2019 there were 20 laws issued by the Legislative Institution. This research discusses the legal politics of the use of imprisonment sanctions in the 2017-2019 legislation. This research is conducted by library research which is descriptive-analytic in nature, namely by describing the contents of the criminal provisions of the 2017-2019 legislation and analysing them. Using a legal political approach with primary data collection methods, namely laws, law books, journals, theses, and other writings. While secondary data from various references that support this research. The results of research on 12 laws that have criminal provisions from 20 laws studied show that imprisonment is the most dominant punishment used in the formulation of criminal threats in each law. The legal politics of the use of imprisonment sanctions in the 2017-2019 legislation when viewed with the 3 main substance of the criminal stelsel shows that based on the type of punishment (strafsoort) the formulation of punishment with the type of ‘Imprisonment and Fines’ is the most widely used formulation. Based on the length and severity of the punishment (strafmaat), it shows that the minimum imprisonment is 3 months and the maximum is 20 years. Regarding fines, it is found that the minimum amount of punishment is Rp. 6,000,000.00 and the maximum amount is Rp. 100,000,000,000.00. Based on the form of criminal punishment (strafmodus), it shows that the form of ‘cumulative punishment’ is the most widely used form of criminal punishment. As for the reasons for the determination of the formulation of punishment in terms of length and severity of punishment, it is not found specifically in the academic paper, except for 1 law that clearly outlines the reasons.